2006
DOI: 10.1088/0954-3899/32/11/015
|View full text |Cite
|
Sign up to set email alerts
|

8Be +14C break-up of22Ne

Abstract: The 12C(18O, 14C + 8Be)8Be reaction was studied at a beam energy of 140 MeV. Two multi-element charged-particle telescopes were used to detect the decay of 22Ne states into 14C + 8Be. The reconstructed excitation energy spectrum indicates that two states at 24.14(20) and 26.89(20) MeV decay by 8Be emission. These states may be linked to a 14C + 2α cluster structure in 22Ne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…4). As was shown in [3], the α-cluster states of 20 Ne and 22 Ne should appear at similar excitation energy, measured with respect to the α-decay threshold, and have similar properties. From this point of view there is a very good agreement between 9 − of 20 Ne at 21.1 MeV (K π =0 − [4]) and 9 − of 22 Ne at 25.0 MeV (present work).…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…4). As was shown in [3], the α-cluster states of 20 Ne and 22 Ne should appear at similar excitation energy, measured with respect to the α-decay threshold, and have similar properties. From this point of view there is a very good agreement between 9 − of 20 Ne at 21.1 MeV (K π =0 − [4]) and 9 − of 22 Ne at 25.0 MeV (present work).…”
Section: Methodssupporting
confidence: 71%
“…Following the successful application of α+ 18 O cluster models in 22 Ne, attempts have been made to extend these models to include more complicated cluster configurations. Earlier evidence [3] indicated that two states in the 22 Ne at 24.14 and 26.89 MeV decay by 8 Be emission (they are indicated by arrows in Fig. 4).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation